Hemodynamic response to exercise and head-up tilt of patients implanted with a Rotary Blood Pump : a computational modeling study - Lim, Einly; Salamonsen, Robert Francis; Mansouri, Mahdi; Gaddum, Nicholas; Mason, David Glen; Timms, Daniel L.; Stevens, Michael Charles; Fraser, John; Akmeliawati, Rini; Lovell, Nigel Hamilton (4 International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc., 2015)
The present study investigates the response of implantable rotary blood pump (IRBP)-assisted patients to exercise and head-up tilt (HUT), as well as the effect of alterations in the model parameter values on this response, using validated numerical models. Furthermore, we comparatively evaluate the performance of a number of previously proposed physiologically responsive controllers, including constant speed, constant flow pulsatility index (PI), constant average pressure difference between the aorta and the left atrium, constant average differential pumppressure, constant ratio between meanpumpflow and pumpflowpulsatility (ratioPI or linear Starling-like control), as well as constant left atrial pressure Pla ( )control, with regard to their ability to increase cardiac output during exercise while maintaining circulatory stability upon HUT. Although native cardiac output increases automatically during exercise, increasing pump speed was able to further improve total cardiac output and reduce elevated filling pressures. At the same time, reduced venous return associated with upright posture was not shown to induce left ventricular (LV) suction. Although Pla control outperformed other control modes in its ability to increase cardiac output during exercise, it caused a fall in the mean arterial pressure upon HUT, which may cause postural hypotension or patient discomfort. To the contrary, maintaining constant average pressure difference between the aorta and the left atrium demonstrated superior performance in both exercise and HUT scenarios. Due to their strong dependence on the pump operating point, PI and ratioPI control performed poorly during exercise and HUT. Our simulation results also highlighted the importance of the baroreflex mechanism in determining the response of the IRBP-assisted patients to exercise and postural changes, where desensitized reflex response attenuated the percentage increase in cardiac output during exercise and substantially reduced the arterial pressure upon HUT.